TINGKAT PENGETAHUAN PASIEN CHRONIC KIDNEY DISEASE (CKD) TERHADAP AKSES HEMODIALISA DAN PERAWATAN AKSES HEMODIALISA DI RSUD DR. PIRNGADI KOTA MEDAN - CAHYANI SHINTIA; MUHAMMAD KHADAFI (JURNAL ILMIAH SIMANTEK, 2021)
Access for hemodialysis is the most important process of Chronic Kidney Disease therapy. Some of the access includingArterivenous Fistula (AVF), Arterivenous Graft (AVG) and Catheterization method. The purpose of this study is to determinethe Chronic Kidney Disease patients’ level of knowledge about hemodialysis accesses and how to take good care of theaccess. The design used in this study is cross sectional, using validated questionnaires towards 60 respondents.The knowledge of the Chronic Kidney Disease patients about the access turns out to be fine, with a result of 50% of thesample which equals to 30 respondents. And the knowledge about taking care of the hemodialysis access has a result of70% which equals to 42 respondents. The Chronic Kidney Disease patients’ level of knowledge about the access and how totake care of it are categorized as good or well done.